GIS-based river flood hazard mapping in rural Area: A case study in Dabong, Kelantan, Peninsular Malaysia - Udin, Wani Sofia; Ismail, Nurul Asyikin; Bahar, Arham Muchtar Achmad; Khan, Mohammad Muqtada Ali (IOS Press, 2018)
Flooding is the most serious natural disaster and often happens in many countries around the world. Dabong Town which is located in the southern district of Kuala Krai, Kelantan was the case study of this research. Floods occur periodically at Kampung Dabong Hulu, Kampung Dabong Hilir and Kampung Chegar Lapan because of the heavy rainfall during the monsoon season. The main objective of this study is to determine which areas are exposed to floods and characterizing the flood zones in the Dabong Town by using Geographic Information System (GIS). Secondary data was gathered from the Department of Irrigation and Drainage while field investigations were conducted at the flooded area. Several questionnaires were distributed to the respondents in order to identify the extent of floods and depth of flooded areas. The results show that three parameters of flood hazards level which are low, medium and high have significant influences on the river flood hazard maps pattern. The area along the Galas River possessed high risk to flood and the total of the high hazard area is 378.39 hectares. Medium hazard area is shown as 57.11 hectares while low hazard area is 37.63 hectares.